Integrated effect of naturopathy and yoga-based interventions on euglycemic hyperinsulinemia among grade 2 obesity: a non-randomized controlled trial - Vaishali Mathapati; K. J. Sujatha; Prashanth Shetty (Traditional Medicine and Modern Medicine)
Background: This study evaluates the impact of an integrated naturopathy and yoga intervention on insulin resistance and metabolic health in individuals with grade 2 obesity, aiming to address modifiable risk factors for Type 2 diabetes. Methodology: Sixty participants were assigned to a control group (standard care) or an intervention group that received a 10-day regimen of integrated Naturopathy and Yoga therapies. Measurements of insulin resistance (HOMA-IR), insulin sensitivity, fasting blood glucose, and body composition were recorded at baseline and after the intervention. Results: The intervention group showed a significant reduction in HOMA-IR and fasting insulin levels, with a marked increase in insulin sensitivity compared to the control group. Body weight, BMI, hip circumference, and body adiposity index decreased significantly in the intervention group, whereas the control group experienced minimal changes. Conclusions: A short-term, integrated naturopathy and yoga regimen effectively reduced insulin resistance and improved key metabolic indicators in grade 2 obese individuals, demonstrating integrated Naturopathy and Yoga as a non-pharmacological approach for managing insulin sensitivity and preventing Type 2 diabetes. This study suggests that lifestyle-based interventions combining naturopathy and yoga can support metabolic health in high-risk populations.Clinical Gtrial Registry: This study is registered with the Clinical Trials Registry-India (CTRI). The registration number for this trial is CTRI/2023/08/05639. CTRI